PENANGGULANGAN SISWA BERMASALAH DENGAN NILAI-NILAI AGAMA ISLAM - Ridhwan M. Daud (FITRAH: International Islamic Education Journal, 2020)
Madrasah ibtidaiyah is a basic level education unit under the auspices of the Ministry of Religion. Students at madrasah ibtidaiyah are between the ages of 6 and 12. The main goal of education at this level is to form a perfect human both physically and psychologically (insan kamil) based on the values ​​of Islamic teachings. This formation can be done because humans are inspired by the potential for good and potential for evil. If there are students who have problems, either regressive or introverted (aloof, shy, timid, sleepy, don't want to go to school) or who are aggressive or extroverted (lying, making trouble, blackmailing friends, violent and behavior that threatens others) in an attempt This formation can use direct educational strategies, namely role models, suggestions and exercises. And the indirect strategy is prohibition, punishment, reward and supervision. Approaches that can be used are the approach of faith, rationality, habituation, gentleness, wisdom and threats.